Implementasi Dakwah Majazi Kyai Febri Eraz Chaniago Di Pesantren Misro Arafah Lubuklinggau - Rama Wijaya Kesuma Wardanni; Pasiaka Pasiska; Citra Gunawan (Jurnal Khabar: Komunikasi dan Penyiaran Islam, 2022)
The implementation of da'wah by majazi febri eraz chaniago is specifically backgrounded on the use of the kiyai febri eraz chaniago da'wah method at the Misro Arafah Islamic Boarding School in Lubuklinggau City. With the aim of knowing the implementation of da'wah majazi Kyai Febri Eraz Chaniago. This research method uses a descriptive method that is used with a qualitative approach, the source of the data is the Asatidz council and students of the Misro Arafah Islamic boarding school in Lubuklinggau City. Data collection is carried out by technique, interview, observation, and documentation. Meanwhile, analysis by means of a process of searching and compiling systematically. It can be concluded that the implementation of majazi proselytizing by approaching it emotionally and using oral, written and deed media as well as, and lectures, texts, manuscripts, and recitations are the methods of proselytizing and the transition of the meaning of essence to other meanings.